Amino‐Acid‐Derived Naphthalenediimides as Versatile G‐Quadruplex Binders. Issue 35 (24th May 2017) - Răsădean, Dora M.; Sheng, Bin; Dash, Jyotirmayee; Pantoş, G. Dan
Abstract: The design and synthesis of water soluble, amino‐acid‐functionalised naphthalenediimides (NDIs) as potential ligands of native G‐quadruplexes is reported. The NDIs were tested on a panel of oncogene promoters, on the human telomeric sequence h‐telo, and on double‐stranded DNA. Out of the ligands tested, NDI3 ( N ϵ ‐Boc‐ l ‐lysine NDI) exhibited a highly discriminating nature by only stabilising the oncogene promoter c‐kit2, which is up‐regulated up to 80 % in ovarian, gastrointestinal, and breast malignancies. Abstract : Selective oncogene stablilisation : Water‐soluble, amino acid functionalised naphthalenediimides are potential ligands of native G‐quadruplexes, and they are tested on a panel of oncogene promoters and against double‐strand DNA. One of the ligands, NDI3, exhibits a highly discriminating nature by stabilising only the oncogene promoter c‐kit2, which is upregulated up to 80 % in ovarian, gastrointestinal, and breast malignancies (see figure).